Web services approach for ambient assisted living in mobile environments - Fernandes, Joel Lourenço (2015)
Web services appeared as a promising technology for Web environments independent of technologies, services, and applications. First, a performance comparison study between the two most used Web service architectures, SOAP and REST, is presented, considering messages exchange between clients and a server. Based on this study, the REST architecture was chosen to deploy the system because it gets better results compared to SOAP architecture. Currently, there are some issues related with this approach that should be studied. For instance, if massive quantities of data are sent to databases it can influence significantly the performance of the whole system. The Advanced Message Queuing Protocol (AMPQ) appears as a promising solution to address this problem. Then, in order to evaluate the performance of this approach, this work presents a performance evaluation and a comparison study of RESTful Web services and the AMQP Protocol considering exchanging messages between clients and a server. The study is based on the averaged exchanged messages for a certain period of time. It was observed and concluded that, for large quantities of messages exchange, the best results comes from the Advanced Message Queuing Protocol. Message Queuing Telemetry Transport (MQTT) was addressed in this work because it is a similar protocol to AMQP but it can be used by mobile devices with a processing capacity smallest unlike the AMQP that needs greater processing capacity. These studies are performed in the context of Ambient Assisted Living environments, since the work was applied to this topic in order to experiment the effectiveness and evaluate the performance of these protocols in this scenario.